Transforming disability studies through legal perspectives in Malaysia - Md Tah, Ikmal Hisham; Mokhtar, Khairil Azmin (International Society of Applied Sciences and TextRoad Journals, 2017)
Disability studies has created much interest from the various academic field to explore including medicine, and in most social sciences specialisation. These areas have become major threshold in understanding the needs of this minority groups where there is debated between two models; medical and social which best-represented disability. With the existence of the Convention on the Rights of Persons with Disabilities (CRPD), a specific international human rights treaty that addressed their affairs, legal perspective has penetrated into forming a new understanding of disability studies. The concept of rights, for example, has become major discussion and debatable within the social model of disability which forms a major understanding of the latter. Thıs article asserts that legal perspective has strengthened the flourish of disability studies as potential academic discourse in future either globally or locally. Malaysia as Sate Members of the CRPD has enacted a domestic legislation known as Persons with Disabilities Act 2008 to fulfil the obligations under the treaty. This paper, based on doctrinal legal research, will explore the potential of transforming disability studies within the context of Malaysian legal framework to show the possible link of this two studies which will benefit not just in academic discourse but also in practical aspects of promoting and protecting the rights of persons with disabilities. The authors call for the need to strengthen disability studies through legal perspectives where it would allow greater and meaningful participation from whole society to address the concern and grievances suffer by this marginalize group.